Open Problem Based Geometry Learning E-Module to Strengthen Creative Thinking Skills - I Ketut Suastika; Sri Hariyani; Nurita Primastya (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Creative thinking is one of the skills that must be developed in the Industrial Revolution 4.0. Students' creative thinking skills still need to be developed. This study aims to create an e-module for learning geometry based on open problems to strengthen the creative thinking skills of PGSD students. This type of research is development research with a design using the Ploom stages. The subjects of the study were PGSD students. The subjects of the small group trial were 18 PGSD students. The data collection method was a questionnaire to obtain quantitative and qualitative data, a trial to test the practicality of the developed e-module, and a Focus Group Discussion (FGD) to collect views and input from material and media experts. The research instruments were a questionnaire and an open-problem competency test. The study results showed that the e-module was validated by media experts, with a percentage of 87%. Material experts validated the e-module, and it showed a rate of 93%. The results of the e-module trial analysis showed that 55% of students met the originality aspect, 28% met the fluency requirements, 72% were flexible, and 83% were elaborative. Teachers should consider e-modules to help increase student interest and engagement. The study's conclusion shows that the developed e-module for geometry learning based on open problem-solving meets the requirements of validity and practicality. The implications of creating an e-module for geometry learning based on open problems for education in general are pedagogy, accessibility, and professional development.